PENGARUH KOMPETENSI, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PERUSAHAAN DAERAH AIR MINUM TIRTA SIAK PEKANBARU - Putra Pratama Dika; Indarti Sri; Roesdi Rosnelly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of competence, motivation and workdiscipline on the performance of the employees of the Tirta Siak Regional Drinking WaterCompany, Pekanbaru City. The population in this study were all 122 employees, and thesample used in this study was 94 people using the Slovin formula. This research wasconducted using primary data collected from respondents through questionnaires as aninstrument to prove the results of the study, to test the hypothesis in this study usingmultiple linear regression analysis with the help of SPSS to see the effect of independentvariables on the dependent variable. The results of this study indicate that the threeindependent variables, namely: competence, motivation and discipline have a significanteffect on employee performance. Competence gives the most dominant influence onemployee performance, followed by motivation and work discipline. The author hopesthat this research can be a reference to improve employee performance to help thecompany achieve its goals. Keywords: Performance, Competence, Motivation, Work Discipline